2011
DOI: 10.1111/j.1464-410x.2011.10113.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of robot‐assisted radical prostatectomy in men with previous transurethral resection of prostate

Abstract: • Surgical, oncological and functional (short-and intermediate-term) outcomes of Group A were compared with 132 cases without previous TURP (Group B). RESULTS• Post TURP patients were found to have significantly greater blood loss (494 vs 324 mL) and a need for bladder neck reconstruction (26.7% vs 9.7%) compared to the non-TURP group.• Surgical time (189 vs 166 min), conversion rate, margin positivity rate and biochemical recurrence rate were also higher.• Incontinence rates were higher both at 6 (14% vs 11.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 16 publications
2
44
0
9
Order By: Relevance
“…Martin et al [12] evaluated 24 patients receiving RALP who had a history of previous treatment to the prostate compared to 486 men without previous treatment and concluded that a history of previous treatment of the prostate does not seem to compromise the perioperative outcomes of RALP. Gupta et al [13] compared outcomes of RALP in 26 patients with TURP to 132 cases of RALP without TURP and discovered a longer operating time, higher operative difficulty and hampered oncological or continence outcomes. Zugor et al [14] used a match-paired analysis to compare 80 cases with previous TURP with an equivalent number of controlled patients and reported that technically more demanding, a prolonged operative time and time interval before continence and potency returns in patients with a previous TURP.…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al [12] evaluated 24 patients receiving RALP who had a history of previous treatment to the prostate compared to 486 men without previous treatment and concluded that a history of previous treatment of the prostate does not seem to compromise the perioperative outcomes of RALP. Gupta et al [13] compared outcomes of RALP in 26 patients with TURP to 132 cases of RALP without TURP and discovered a longer operating time, higher operative difficulty and hampered oncological or continence outcomes. Zugor et al [14] used a match-paired analysis to compare 80 cases with previous TURP with an equivalent number of controlled patients and reported that technically more demanding, a prolonged operative time and time interval before continence and potency returns in patients with a previous TURP.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,9 For RALP, 200 and 189 minutes after transurethral resection and 186 and 166 minutes without previous surgery were reported. 13,14 Irrespective of whether a laparoscopic or open approach was used, previous TURP was associated with a significant increase in mean operative time, ranging from 8 to 31 minutes. Clinically, standard deviations of 44 to 105 minutes may indicate more complicated intraoperative procedures in individual cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the mean estimated blood loss ranged from a minimum of 212 -163 mL to a maximum of 884 -565 mL for laparoscopic procedures, 10,18 from 790 -425 mL to 1374 -679 mL for open RRP, 5,9 and from 155 to 494 mL for RALP. 13,14 In the literature, open RRP after previous prostate surgery is associated with transfusion rates varying from 0% to 46%. 5,9 Only one study reported that LRP patients (3.4%) needed transfusions during LRP after previous surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations